2017
DOI: 10.1259/bjr.20160477
|View full text |Cite
|
Sign up to set email alerts
|

Biological dose-escalated definitive radiation therapy in head and neck cancer

Abstract: Objective: To compare treatment outcome of patients with head and neck (HN) tumours treated with definitive radiation therapy that, mainly owing to differences in the fractionation scheme used with simultaneous integrated boost techniques, resulted in a different biological dose. Methods: 181 patients with HN cancer, prescribed to about 70.2 Gy in the primary tumour, were included in this study. Population cohort was divided into Group ,70 and Group $70 when the mean dose converted to a 2 Gy fractionation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Except for escalated radiation dosage, SIB technique might be another underlying reason for improved loco-regional control, as it allowed for a maximum of 65Gy EBRT to be delivered at 2.6Gy per fraction within a median OTT of 46.5 days [30]. In Guckenberger' study, increased dose per fraction and reduced OTT through SIB allowed for an iso-toxic dose escalation of 8.0 Gy on average, which consequently yielded an improved tumor control probability from 15-28% [31].…”
Section: Discussionmentioning
confidence: 99%
“…Except for escalated radiation dosage, SIB technique might be another underlying reason for improved loco-regional control, as it allowed for a maximum of 65Gy EBRT to be delivered at 2.6Gy per fraction within a median OTT of 46.5 days [30]. In Guckenberger' study, increased dose per fraction and reduced OTT through SIB allowed for an iso-toxic dose escalation of 8.0 Gy on average, which consequently yielded an improved tumor control probability from 15-28% [31].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that IMRT boost was highly effective in nodal sterilization; it should be considered as an indispensable component of treatment for LACC, especially when positive nodes were present. Except for escalated radiation dosage, SIB technique might be another underlying reason for improved locoregional control, as it allowed for a maximum of 65 Gy EBRT to be delivered at 2.6 Gy per fraction within a median OTT of 46.5 days [30]. In Guckenberger' study, increased dose per fraction and reduced OTT through SIB allowed for an iso-toxic dose escalation of 8.0 Gy on average, which consequently yielded an improved tumor control probability from 15 to 28% [31].…”
Section: Distant Metastasismentioning
confidence: 99%
“…Several early clinical trials have studied the role of radiation dose intensification to the primary tumor and metastatic lymph nodes in order to improve local control for HNSCC (5)(6)(7). However, concern still exists about excessive acute and late toxicities of this approach and therefore no large randomized trial has been conducted so far.…”
Section: Introductionmentioning
confidence: 99%